The Efficient Optimization of a Protein Expression by Design of Experiment (Journal of Fiber Bioengineering and Informatics, 2015)
In terms of the prokaryotic expression system Escherichia coli, it is well-known that incubation\rtemperature, OD_{600} value, isopropyl thiogalactoside concentration and time of induction are general\rfactors which can directly affect the final protein's expression. The traditional method for this\roptimization is to study these factors which may influence the protein expression separately, thus,\rthe interactions between factors are ignored. Design of experiment is a time-saving and cost-effective\rmethodology for increasing the productivity and improving the quality of a product. In order to verify\rif design of experiment is suitable for the optimization of a protein expression and also to reveal if there\ris any interaction between the factors that have a significant influence on the protein's expression, the\roptimization of expression for the protein Bmlebocin3 was carried out using the design of experiment\rconcept. Bmlebocin3 is an antimicrobial peptide in the silkworm, Bombyx mori. It has a unique precursor\rform which was suitable for this investigation. In this study, the Bmlebocin3 gene was cloned and\rexpressed in Escherichia coli, and then this expression was optimized by design of experiment. The results\rrevealed that through the use of design of experiment, in addition to quantifying the separate effects\rof the OD_{600} value and the time of induction, it demonstrated that, their interaction can significantly\raffect the expression of Bmlebocin3. Furthermore, the best condition for the Bmlebocin3 's expression\rwas identified through fewer experiments. This proved that design of experiment can be used as an\refficient way to optimize the protein expression.
Keywords: DoE; Vector Construction; Optimization; Protein Expression; Bmlebocin3